Computer vision, imaging and computer graphics -- theory and applications : 12th International Joint Conference, VISIGRAPP 2017, Porto, Portugal, February 27-March 1, 2017, Revised selected papers /: 12th International Joint Conference, VISIGRAPP 2017, Porto, Portugal, February 27-March 1, 2017, Revised selected papers. (2019) - Unknown
No abstract available